Symmetry constraints mediate the learning and transfer of bimanual coordination patterns across planes of motion - Temprado, J. J.; Swinnen, S. P.; Cutton-Jean, C.; Salesse, R. (Journal of Motor Behavior, 2007)
The authors investigated whether neuromuscular and directional constraints are dissociable limitations that affect learning and transfer of a bimanual coordination pattern. Participants (N = 9) practiced a 45° muscular relative phasing pattern in the transverse plane over 4 days. The corresponding to-be-learned spatial relative phasing was 225°. Before, during, and following practice, the authors administered probe tests in the sagittal plane to assess transfer of learning. In the probe tests, participants performed various patterns characterized by different muscular and spatial relative phasing (45°, 45°, 45°, 225°, 225°, 45°, and 225°, 225°). The acquisition of the to-be-learned pattern in the transverse plane resulted in spontaneous positive transfer of learning only to coordination patterns having 45° of spatial relative phase, irrespective of muscular phasing. Moreover, transfer occurred in the sagittal plane to coordination patterns that had symmetry properties similar to those of the to-be-learned pattern. The authors conclude that learning and transfer of spatial features of coordination patterns from the transverse to the sagittal plane of motion are mediated by mirror-symmetry constraints.